Detection of human enteric viral genes in a non-native winter crane fly, Trichocera maculipennis (Diptera) in the sewage treatment facilities at Antarctic stations - Lee, Sook-Young; Kim, Ji Hee; Kang, Seunghyun; Park, Kye Chung; Cho, Sung Mi; Salinas, Carla Ximena; Rebolledo, Lorena; Benitez, Hugo A.; Contador Mejias, Tamara Andrea; Soutullo, Alvaro; Juri, Eduardo; Kim, Sanghee (My University, 2024)
BackgroundThe Antarctic environment is susceptible to the introduction of non-native species due to its unique ecosystem, which has evolved under geographical isolation and extreme climatic conditions over an extended period. The recent introduction of the non-native winter crane fly, Trichocera maculipennis, to maritime Antarctica may pose a potential threat to the Antarctic ecosystem. In this study, we evaluated the possibility of the mechanical transmission of viruses by T. maculipennis.MethodsWe assessed the potential for the mechanical transmission of viruses using next-generation sequencing (NGS), quantitative PCR (qPCR), and virus isolation methods from T. maculipennis (Tm)-related samples (Tm body-wash fluid and Tm body-ground samples) collected from habitats and sewage treatment facilities located at three research stations in Antarctica.ResultsVirome analysis detected the genomic fragments of human adenovirus (AdV) and human endogenous retrovirus (HERV) in Tm-related samples. These viruses are commonly found in human feces. In addition, plant viruses, such as pepper mild mottle virus (PMMoV) and cucumber green mottle mosaic virus (CGMMV), both known indicators of enteric viruses, were identified in all Tm-related samples, likely originating from wastewater. However, the low quantities of AdV and HERV genomes detected in Tm-related samples through qPCR, coupled with the non-viability of AdV in virus isolation tests, indicate that T. maculipennis has limited potential for mechanical transmission under the conditions in the studies.ConclusionsOur study represents the first evaluation of the potential risk of non-native species serving as vectors for viral pathogens in Antarctica. Although the viruses detected were in relatively low quantities and non-viable, this study highlights the importance of further evaluating the risks associated with non-native species, particularly as the likelihood of their introduction increases to Antarctica due to climate change and increased human activity.
Keywords: trichocera maculipennis; non-native winter crane fly; antarctica; virus; mechanical transmission